2018
DOI: 10.5539/jsd.v11n1p13
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of NYSC Community Development Service: Empirical Evidences from Southwestern Nigeria

Abstract: Community development service is one of the cardinal programmes of NYSC sheme. However, it appears to be one of the challenging aspects of NYSC Scheme. This study therefore analysed challenges confronting NYSC scheme in the delivery of community development service in Southwestern Nigeria. Data were obtained from both primary and secondary sources. This study concluded that poor financing (65.4%), Lack of good ideas (67.8%), inadequate sensitization on NYSC community development service operations/functions (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…lack of understanding among group member; lack of interest by corps members; lack of operational facilities; lack of motivation/incentive by the CDS coordinators; too many lines of action/project to be executed; problem of leadership/mode of leadership structure/s; fear of area boys attack/kidnapping; lack of CDS operational fund/capital and sensitization on CDS operations/functions. This is in line with the study Lamidi, Benson and Adisa [3] whose findings on challenges on NYSC Community Development Service in Southwestern Nigeria listed as lack of good ideas; inadequate sensitization of NYSC Community Development Service (CDS).…”
Section: Discussionsupporting
confidence: 88%
“…lack of understanding among group member; lack of interest by corps members; lack of operational facilities; lack of motivation/incentive by the CDS coordinators; too many lines of action/project to be executed; problem of leadership/mode of leadership structure/s; fear of area boys attack/kidnapping; lack of CDS operational fund/capital and sensitization on CDS operations/functions. This is in line with the study Lamidi, Benson and Adisa [3] whose findings on challenges on NYSC Community Development Service in Southwestern Nigeria listed as lack of good ideas; inadequate sensitization of NYSC Community Development Service (CDS).…”
Section: Discussionsupporting
confidence: 88%
“…Through this programme, many corps members have in the past been able to provide healthcare, education, infrastructure development (such as road construction, borehole drilling, etc. ), transportation and road safety, food and agriculture, and many other services relevant in community development (Lamidi, 2017;National Youth Service Corps Handbook, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, over the years, there have been calls from different quarters for the review, amendment or even scrapping of the NYSC scheme (Obadare, 2005;Oluwalogbon, 2019). This is despite a number of studies that have shown numerous gains and positive roles the NYSC scheme have played in line with its objectives, and in the area of community development Lamidi, 2017). This is probably because over the years, sufficient studies have not effectively highlighted the direct roles the NYSC concept, for instance the CDS groups, have had in community development.…”
Section: Introductionmentioning
confidence: 99%
“…Past evaluation studies of the scheme were often shallow, by covering specific areas of the programme. [11][12][13] Others often drew information from a small sample of respondents in specific regions. [14][15][16] This is the first attempt to obtain a largescale data covering the 37 camps and focusing on about all the areas of NYSC.…”
Section: Introductionmentioning
confidence: 99%